In-plane thermal conductivity of multi-walled carbon nanotube yarns under mechanical loading - Goh, B.; Kim, K. J.; Park, C. L.; Kim, E. S.; Kim, S. H.; Choi, J.
We present a computational and experimental study of the in-plane heat transfer behavior of a coiled multi-walled carbon nanotube (MWCNT)yarn. The surface temperature of the MWCNT yarn in contact with the high-temperature wire is measured to verify that the thermal conductivity in the radial direction (TCRD)of the coiled MWCNT yarn is high enough to be captured by a thermal imaging camera. A significant change in the TCRD is observed under mechanical strain in particular. Furthermore, the in-plane heat flow of MWCNTs is studied using molecular dynamics simulations. The results confirm that the structural deformation of interstitial spaces between MWCNTs during mechanical loading is a key factor in explaining the heat transfer paths generated by the thermal vibrations of carbon atoms. It is also confirmed that the change in TCRD is reduced owing to an increase in the radial buckling strength of the yarn comprising MWCNTs of a smaller diameter. The TCRD change is crucial in MWCNT-yarn applications such as twistron energy harvesters
Keywords: MULTI-WALLED CARBON NANOTUBE YARN; IN-PLANE THERMAL CONDUCTIVITY; MOLECULAR DYNAMICS SIMULATION; STRUCTURAL DEFORMATION; CURVATURE EFFECT